Urethane (meth)acrylate

Urethane (meth)acrylates, formed from polyalkylene glycol mono(meth)acrylates and polyisocyanates, address the challenge of poor low-temperature curing in polymers used for liquid crystal and organic electroluminescent displays, achieving efficient and contamination-free curing.

JP7661720B2Active Publication Date: 2025-04-15NOF CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021029138
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-25
Publication Date
2025-04-15
Estimated Expiration
2041-02-25

AI Technical Summary

Technical Problem

Existing polymers used in the manufacturing of liquid crystal displays and organic electroluminescent displays have poor low-temperature heat-curing properties, leading to reduced productivity and potential contamination of liquid crystal components during the curing process.

Method used

Development of urethane (meth)acrylates, which are the reaction products of polyalkylene glycol mono(meth)acrylates and polyisocyanates, specifically designed to exhibit excellent low-temperature thermal curability and rapid hardness development.

Benefits of technology

The urethane (meth)acrylates achieve rapid curing and desired hardness at low temperatures (around 60°C), improving manufacturing efficiency and preventing contamination of liquid crystal components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007661720000003
    Figure 0007661720000003
  • Figure 0007661720000001
    Figure 0007661720000001
  • Figure 0007661720000002
    Figure 0007661720000002
Patent Text Reader

Abstract

To provide a polymer which has a preferable thermosetting property at a low temperature and can quickly reach desired curing from curing start.SOLUTION: There is provided an urethane (meth)acrylate which is a reaction product of following components (A) and (B): (a component A) a polyalkylene glycol mono(meth)acrylate represented by a formula (1): CH2=CR-COO-(AO)n-H in which a ratio wb / wf between wb and wf calculated from a chromatogram determined by gel permeation chromatography satisfies a relation of the expression (2): 0.25≤wb / wf≤0.90, (definitions of signals in the formulas (1) and (2) are as described in the specification); and (a component B) a polyisocyanate.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a urethane (meth)acrylate having good low-temperature curing properties. Here, the term "urethane (meth)acrylate" means a compound having a urethane bond and a (meth)acryloyl group. [Background technology]

[0002] In recent years, flat panel displays using various display elements have been developed and manufactured in the electronics and electrical industries. Examples include liquid crystal (LC) displays and electroluminescence (EL) displays. A liquid crystal display element is composed of a substrate such as glass or a plastic film, a frame-shaped cured sealant sandwiched between the substrate and the cured sealant, and a display element layer enclosed within the region surrounded by the cured sealant. Thermosetting epoxy resins have traditionally been used as sealants for liquid crystal displays. However, thermosetting epoxy resins require long-term heating and curing at high temperatures (150 to 180°C), which has led to reduced productivity.

[0003] In addition, EL displays can be made thinner and lighter, and are attracting attention as a new type of flat panel display. EL display elements include inorganic EL elements and organic EL elements. Organic EL elements are superior to inorganic EL elements in terms of high brightness, high efficiency, fast response, and multicolorization, but have low heat resistance, with a heat resistance temperature of about 60 to 80°C. For this reason, there is a problem that thermosetting epoxy resins, which require heating at high temperatures, do not cure sufficiently as a sealing material for organic EL displays.

[0004] To solve these problems, a photocurable resin that does not require heat curing can be used, but when light of less than 350 nm is irradiated to cure the photocurable resin, the organic dye of the organic EL element deteriorates, resulting in insufficient emission intensity. Therefore, a thermosetting resin that can be cured at low temperatures is being studied. For example, Patent Document 1 discloses an adhesive composition that can be cured at low temperatures, which contains (a) a urethane compound having at least one (meth)acryloyl group, (b) a compound having at least two (meth)acryloyl groups, and (c) an organic peroxide having a one-hour half-life temperature of 70 to 115°C. The "one-hour half-life temperature of the organic peroxide" is defined in Patent Document 1 as "the decomposition temperature at which the organic peroxide obtains a one-hour half-life". [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2015-140409 A Summary of the Invention [Problem to be solved by the invention]

[0006] In recent years, there has been a demand for polymers that can be thermoset at low temperatures (for example, about 60°C). However, when an organic peroxide with a low one-hour half-life temperature as described in Patent Document 1 is used to improve thermoset properties at low temperatures, the stability of a composition containing such an organic peroxide and a polymer may decrease. In addition, when a composition containing a polymer that is slow to reach a desired hardness is used to manufacture a product containing a liquid crystal component, the uncured components of the composition may dissolve into the liquid crystal component during heating, thereby contaminating the liquid crystal component. For these reasons, there has been a demand for a polymer that improves thermoset properties at low temperatures and quickly reaches a desired hardness from the start of curing. [Means for solving the problem]

[0007] An object of the present invention is to provide a polymer which has good thermosetting properties at low temperatures and can quickly reach a desired hardness from the start of curing.

[0008] The present invention capable of achieving the above object is as follows. [1] A urethane (meth)acrylate which is the reaction product of component A and component B shown below: (Component A) Formula (1): CH2=CR-COO-(AO) n -H (1) In formula (1), R represents a hydrogen atom or a methyl group, AO represents at least one oxyalkylene group having 2 to 4 carbon atoms, and when two or more AO are present, (AO) n The addition form of may be either block or random, and n represents the average number of moles of oxyalkylene groups added and is a number from 5 to 100. is expressed as w calculated from the chromatogram obtained by gel permeation chromatography measurement. b And w f The ratio of b / w f But equation (2): 0.25≦w b / w f ≦0.90 (2) (In formula (2), the retention time at the maximum peak height (h) in the chromatogram peak is t h and 1 / 10 of the maximum peak height (h 1 / 10 ) two retention times at t f and t b (However, t f <t b ), then w f is h and f Difference from (t h -t f ), and w b is b and h Difference from (t b -t h ) A polyalkylene glycol mono(meth)acrylate satisfying the relationship: (Component B) Polyisocyanates. Effect of the Invention

[0009] The urethane (meth)acrylate of the present invention has excellent thermosetting properties at low temperatures (for example, about 60° C.), and can quickly reach a desired hardness from the start of curing. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a model of a chromatogram obtained by gel permeation chromatography measurement of a polyalkylene glycol mono(meth)acrylate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will be described in detail below. In this specification, a numerical range defined using the symbol "~" includes both ends (upper and lower limits) of the symbol "~". For example, "2-4" means 2 or more and 4 or less. In this specification, "(meth)acrylate" means "acrylate or methacrylate". Here, only one type of (meth)acrylate may be used, or two or more types may be used in combination. The term "(meth)acryloyl group" and the like also have the same meaning as "(meth)acrylate".

[0012] (Component A) The present invention relates to a compound represented by the formula (1): CH2=CR-COO-(AO) n -H (1) In formula (1), R represents a hydrogen atom or a methyl group, AO represents at least one oxyalkylene group having 2 to 4 carbon atoms, and when two or more AO are present, (AO) n The addition form of may be either block or random, and n represents the average number of moles of oxyalkylene groups added and is a number from 5 to 100. The component A may be used alone or in combination of two or more kinds.

[0013] AO represents at least one oxyalkylene group having 2 to 4 carbon atoms. That is, AO is at least one selected from the group consisting of an oxyethylene group, an oxypropylene group, and an oxybutylene group. AO is preferably an oxypropylene group. n is the average number of moles of oxyalkylene groups added. Therefore, n may be a decimal number. n is preferably 5 to 60, more preferably 5 to 50, further preferably 5 to 40, and particularly preferably 15 to 40.

[0014] Component A is calculated from a chromatogram (vertical axis: refractive index intensity, horizontal axis: retention time) obtained by gel permeation chromatography (GPC) measurement using a differential refractometer. b And w f The ratio of b / w f But equation (2): 0.25≦w b / w f ≦0.90 (2) (In formula (2), the retention time at the maximum peak height (h) in the chromatogram peak is t h and 1 / 10 of the maximum peak height (h 1 / 10 ) two retention times at t f and t b (However, t f <t b ), then w f is h and f Difference from (t h -t f ), and w b is b and h Difference from (t b -t h ) The above relationship is satisfied (see FIG. 1).

[0015] Component A w b / wf When w is smaller than 0.25, the viscosity of the urethane (meth)acrylate, which is the reaction product of component A and component B, becomes high, and the handling properties become poor. b / w f When w is larger than 0.90, the reactivity of the urethane (meth)acrylate decreases, and the curing property decreases. b / w f is preferably 0.30 to 0.80, and more preferably 0.35 to 0.60.

[0016] w b / w f The chromatogram (vertical axis: refractive index intensity, horizontal axis: retention time) for calculating the above was obtained using an HLC-8320GPC (registered trademark) gel permeation chromatography (GPC) system, a SHODEXKF-G guard column, and three SHODEXKF804L columns in series, with the column temperature set at 40° C. and tetrahydrofuran as the developing solvent flowing at a flow rate of 1 mL / min, and 0.1 mL of a 0.1 wt % solution of polyalkylene glycol mono(meth)acrylate in tetrahydrofuran, using an EcoSECGPC calculation program.

[0017] Component A can be produced by adding at least one selected from the group consisting of ethylene oxide, propylene oxide and butylene oxide (preferably propylene oxide) to a starting material (e.g., 2-hydroxypropyl (meth)acrylate) in the presence of a composite metal cyanide complex catalyst (hereinafter sometimes abbreviated as "DMC catalyst"). Specifically, the starting material and the DMC catalyst are added to a reaction vessel, and at least one selected from the group consisting of ethylene oxide, propylene oxide and butylene oxide (hereinafter collectively referred to as "alkylene oxide having 2 to 4 carbon atoms") is added continuously or intermittently under stirring in an inert gas atmosphere to perform addition polymerization. The alkylene oxide having 2 to 4 carbon atoms may be added under pressure or atmospheric pressure.

[0018] There is no limitation on the average supply rate of the alkylene oxide having 2 to 4 carbon atoms, but it is preferable to change it depending on the charged amount of the alkylene oxide having 2 to 4 carbon atoms. When V1 is the supply rate (supply amount per unit time) during which 5% by weight or more and 20% by weight or less of the total supply amount of the alkylene oxide having 2 to 4 carbon atoms is supplied, V2 is the supply rate during which more than 20% by weight and 50% by weight or less of the total supply amount of the alkylene oxide having 2 to 4 carbon atoms is supplied, and V3 is the supply rate during which more than 50% by weight and 100% by weight or less of the total supply amount of the alkylene oxide having 2 to 4 carbon atoms is supplied, in one embodiment for producing component A, it is preferable to control the average supply rate of the alkylene oxide having 2 to 4 carbon atoms so that V1 / V2=1.1 to 2.0 and V2 / V3=1.1 to 1.5. In another embodiment for producing component A, it is preferable to control the average supply rate of the alkylene oxide having 2 to 4 carbon atoms so that V1 / V2=0.4 to 0.9 and V2 / V3=0.5 to 0.95.

[0019] The reaction temperature for adding an alkylene oxide having 2 to 4 carbon atoms to the starting material is preferably 50° C. to 120° C., and more preferably 70° C. to 90° C. If the reaction temperature is lower than 50° C., the reaction rate is very slow, and if it is higher than 120° C., problems such as polymerization of the polymerizable groups in the starting material and coloring occur.

[0020] There are no particular limitations on the trace amounts of water contained in the starting materials and the alkylene oxide having 2 to 4 carbon atoms, but it is desirable that the amount of water contained in the starting materials is 0.5% by weight or less, and the amount of water contained in the alkylene oxide having 2 to 4 carbon atoms is 0.01% by weight or less.

[0021] The amount of the DMC catalyst used is not particularly limited, but is preferably 0.0001 to 0.1 parts by weight, more preferably 0.001 to 0.05 parts by weight, based on 100 parts by weight of the alkylene oxide derivative (i.e., component A) produced. The DMC catalyst may be added to the reaction system all at once at the beginning, or may be added in succession in portions. After the polymerization reaction is completed, the DMC catalyst is removed. The catalyst can be removed by a known method such as filtration, centrifugation, or treatment with a synthetic adsorbent. In the production of component A, a known DMC catalyst can be used.

[0022] The DMC catalyst is, for example, a compound represented by the formula (3): M a [M' x (CN) y ] b (H2O) c (L) d (3) (In formula (3), M and M' represent metal atoms, L represents an organic ligand, and a, b, c, d, x, and y represent positive integers.) It is possible to use those represented by the following formula:

[0023] Examples of the metal atom (metal cation) M include Zn(II), Fe(II), Fe(III), Co(II), Ni(II), Al(III), Sr(II), Mn(II), Cr(III), Cu(II), Sn(II), Pb(II), Mo(IV), Mo(VI), W(IV), W(VI), etc. Of these, Zn(II) is preferably used.

[0024] Examples of the metal atom (metal cation) M' include Fe(II), Fe(III), Co(II), Co(III), Cr(II), Cr(III), Mn(II), Mn(III), Ni(II), V(IV), V(V), etc. Among these, Fe(II), Fe(III), Co(II), and Co(III) are preferably used.

[0025] As the organic ligand L, for example, alcohol, ether, ketone, ester, etc. can be used, and alcohol is more preferable. Preferred organic ligands are water-soluble, and specific examples include tert-butyl alcohol, n-butyl alcohol, iso-butyl alcohol, N,N-dimethylacetamide, ethylene glycol dimethyl ether (glyme), diethylene glycol dimethyl ether (diglyme), etc. A particularly preferred DMC catalyst is Zn(II)3[Co(III)(CN)6]2(H2O)4(tert-butyl alcohol)2 coordinated with tert-butyl alcohol.

[0026] In the reaction of adding an alkylene oxide having 2 to 4 carbon atoms to the starting material, other additives may be used. For example, hydroquinone (HQ), hydroquinone monomethyl ether (MQ), 2,6-di-tert-butylhydroxytoluene (BHT), di-tert-butylhydroxyanisole (BHA), α-tocopherol, β-tocopherol, γ-tocopherol, or the like may be added to the reaction system as a polymerization inhibitor. The polymerization inhibitor is preferably MQ and / or BHT, more preferably BHT. The amount of the polymerization inhibitor added is preferably 0.001 to 0.3 parts by weight per 100 parts by weight of the total of the starting material (e.g., 2-hydroxypropyl (meth)acrylate) and the alkylene oxide having 2 to 4 carbon atoms. If the amount added is less than 0.001 part by weight, the function of the polymerization inhibitor becomes insufficient, and gelation may occur during the addition of the alkylene oxide having 2 to 4 carbon atoms. On the other hand, if the amount added is more than 0.3 parts by weight, the purity of the obtained polyalkylene glycol mono(meth)acrylate may decrease.

[0027] (Component B) In the present invention, a polyisocyanate is used as component B. Here, polyisocyanate means a compound having two or more isocyanate groups (also known as isocyanato groups). Only one type of component B may be used, or two or more types may be used in combination.

[0028] The polyisocyanate may be any one of an aliphatic polyisocyanate, an alicyclic polyisocyanate and an aromatic polyisocyanate, and may be a mixture of these.

[0029] Examples of diisocyanates (i.e., bifunctional isocyanates) include aromatic diisocyanates such as 1,4-tolylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 1,3-xylylene diisocyanate, 1,5-naphthalene diisocyanate, and 4,4'-diphenylmethane diisocyanate, and aliphatic diisocyanates and alicyclic diisocyanates such as trimethylene diisocyanate, hexamethylene diisocyanate, 1,4-cyclohexane diisocyanate, dicyclohexylmethane diisocyanate, isophorone diisocyanate, and norbornane diisocyanate.

[0030] Examples of triisocyanates (i.e., trifunctional isocyanates) include isocyanurates (i.e., trimers of diisocyanates) obtained from diisocyanates, adducts obtained by adduct modification of diisocyanates, and reaction products of diisocyanates and trihydric alcohols (e.g., glycerin, trimethylolpropane, etc.). Examples of diisocyanates that can be used to obtain triisocyanates include those mentioned above.

[0031] Examples of tri- or higher functional polyisocyanates include reaction products of the above-mentioned diisocyanates with polyols or polyamines.

[0032] As component B, aliphatic diisocyanates, alicyclic diisocyanates, and isocyanurates obtained therefrom (i.e., trimers of aliphatic diisocyanates, and trimers of alicyclic diisocyanates) are preferred, and hexamethylene diisocyanate, dicyclohexylmethane diisocyanate, isophorone diisocyanate, norbornane diisocyanate, and isocyanurates obtained therefrom are more preferred.

[0033] (Urethane (meth)acrylate) The urethane meth(acrylate) of the present invention is a reaction product between the component A and the component B. Hereinafter, the production method of the urethane meth(acrylate) of the present invention (i.e., the reaction between the component A and the component B) will be described in order.

[0034] The reaction temperature of the component A and the component B is, for example, 20°C to 120°C, and preferably 40°C to 100°C.

[0035] In the reaction between the component A and the component B, a known urethanization catalyst may be used as necessary. The urethanization catalyst may be used alone or in combination of two or more. Examples of the urethanization catalyst include amines such as pyridine, triethylamine, diethylamine, and dibutylamine, phosphines such as tributylphosphine and triphenylphosphine, naphthenates such as copper naphthenate, cobalt naphthenate, and zinc naphthenate, metal alkoxides such as tributoxyaluminum, trititanium tetrabutoxide, and zirconium tetrabutoxide, Lewis acids such as aluminum chloride, and tin compounds such as 2-ethylhexanetin, octyltin trilaurate, dibutyltin dilaurate, and octyltin diacetate.

[0036] As the urethanization catalyst, a tin compound is more preferable since the reaction can be accelerated by adding a small amount. The amount of the urethanization catalyst used is preferably 0.005 to 1 part by weight, more preferably 0.01 to 0.5 parts by weight, based on 100 parts by weight in total of the component A and the component B.

[0037] The molar ratio (OH / NCO) of the hydroxyl group (OH) in the component A to the isocyanate group (NCO) in the component B is preferably 0.80 to 1.20, and more preferably 0.90 to 1.20.

[0038] The isocyanate group content in the urethane (meth)acrylate of the present invention is preferably 0 to 3% by weight, more preferably 0 to 1% by weight.

[0039] The reaction between the component A and the component B can be carried out by, for example, charging the component A and the component B all at once in a reactor and reacting them together, adding the component A dropwise to the component B, or adding the component B dropwise to the component A.

[0040] The urethane (meth)acrylate of the present invention can be cured using a known thermal polymerization initiator.

[0041] The amount of the thermal polymerization initiator used is preferably 0.1 to 5 parts by weight, and more preferably 0.1 to 3 parts by weight, based on 100 parts by weight of the urethane (meth)acrylate. EXAMPLES

[0042] The present invention will now be described in more detail with reference to examples.

[0043] Example 1 (1) Synthesis of component A 651g of 2-hydroxypropyl acrylate (water content 0.02% by weight), 1.0g of DMC catalyst (Zn(II)3[Co(III)(CN)6]2(H2O)4(tert-butyl alcohol)2), and 1.2g of 2,6-di-tert-butylhydroxytoluene (BHT) were charged into a 5-liter (capacity 4,890mL) stainless steel pressure-resistant reactor equipped with a thermometer, pressure gauge, safety valve, nitrogen gas inlet, stirrer, vacuum exhaust tube, cooling coil, and steam jacket. After nitrogen replacement, the temperature was raised to 80°C, and 581g of propylene oxide (methyl oxirane, water content 0.005% by weight) was added dropwise from the nitrogen gas inlet while stirring under conditions of 0.3 MPa or less. The pressure and temperature changes over time in the reactor were observed, and the pressure in the reactor was found to have suddenly decreased 5 hours after the end of the dropwise addition of 581g of propylene oxide. Thereafter, while maintaining the inside of the reaction tank at 80°C, 1130 g of propylene oxide was gradually dropped from the nitrogen gas inlet tube under conditions of 0.5 MPa or less. The average supply rates were V1 260 g / hour, V2 290 g / hour, and V3 350 g / hour (V1 / V2 = 0.9, V2 / V3 = 0.8). After the dropwise addition, the reaction was allowed to proceed at 80°C for 0.5 hours, after which the reaction mixture was extracted from the reaction layer, and the reaction mixture was filtered to remove solids, thereby obtaining a liquid component A. The obtained component A was subjected to gel permeation chromatography measurement using the above-mentioned HLC-8320GPC (registered trademark). As a result, the w b / w f was 0.50.

[0044] (2) Synthesis of urethane acrylate (UA-1) Into a four-neck flask equipped with a stirrer, an air inlet tube, and a thermometer, the above-mentioned component A (number of repeating units of oxypropylene group = 9, hydroxyl value = 120 mg KOH / g)365g of hexamethylene diisocyanate, 135g of isocyanurate of hexamethylene diisocyanate (i.e., trimer of hexamethylene diisocyanate, Duranate TPA-100, manufactured by Asahi Kasei Corporation, NCO content: 23% by weight), and 0.05g of dibutyltin dilaurate were added. The molar ratio of hydroxyl group (OH) / isocyanate group (NCO) at this time was 1.05. Next, while blowing in air, the temperature in the four-neck flask was kept at 60°C and reacted for 4 hours. After that, it was confirmed by the method of JISK1603-1 that the isocyanate group content was 0.05% by weight or less and that almost all of the isocyanate groups had reacted with the hydroxyl groups to form urethane bonds, and 500g of urethane acrylate (UA-1) was obtained.

[0045] Comparative Example 1 (1) Synthesis of component A' 500g of 2-hydroxypropyl acrylate, 14.5g of tin tetrachloride, 0.8g of hydroquinone monomethyl ether (MQ), and 0.2g of 2,6-di-tert-butylhydroxytoluene (BHT) were charged into a stainless steel 5-liter (capacity 4,890mL) pressure-resistant reactor equipped with a thermometer, a pressure gauge, a safety valve, a nitrogen gas inlet tube, a stirrer, a vacuum exhaust tube, a cooling coil, and a steam jacket. After nitrogen replacement, the temperature was raised to 60°C, and 1025g of propylene oxide (methyloxirane) was added dropwise from the nitrogen gas inlet tube while stirring under conditions of 0.3MPa or less. After completion of the dropwise addition, the mixture was reacted at 60°C for 0.5 hours, and after adding water and hexane, neutralization was performed with an aqueous sodium hydroxide solution. After removing the water layer, hexane and water were distilled off under reduced pressure, and the concentrate was filtered to remove solids, to obtain a liquid component A'. The obtained component A' was measured by gel permeation chromatography in the same manner as in Example 1. As a result, the w of the obtained component A' b / w f was 1.34.

[0046] (2) Synthesis of urethane acrylate (UA-1') Instead of the component A obtained in Example 1, the component A' (number of repeating units of oxypropylene group = 9, hydroxyl value = 120 mg KOH / g)A urethane acrylate (UA-1′) was synthesized in the same manner as in Example 1, except that the above was used.

[0047] Evaluation of urethane acrylate The low-temperature curing properties of the urethane acrylate obtained in Example 1 and Comparative Example 1 were evaluated using a viscoelasticity measuring device MCR302 (manufactured by Anton Paar). Specifically, 10 g of the urethane acrylate and 0.02 g of a thermal polymerization initiator ("V-65", 2,2'-azobis(2,4-dimethylvaleronitrile) manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were charged into a screw tube to prepare a reaction mixture. Then, the reaction mixture was heated, and the time from the time when the temperature reached 55°C to the time when the reaction mixture started to cure (i.e., the time when the storage modulus rose sharply) (referred to as "curing start time" in Table 1 below) was measured. After that, heating was continued at 55°C, and the time from the time when the curing started to the time when the storage modulus reached 1000 Pa (referred to as "curing time" in Table 1 below) was measured. The results are shown in Table 1.

[0048] [Table 1]

[0049] As shown in Table 1 ,Nari The curing initiation time and curing time of the urethane acrylate (UA-1) of Example 1 obtained using Part A were ,Nari It was shorter than that of the urethane acrylate (UA-1') of Comparative Example 1 obtained using the part A'.

[0050] Example 2 Synthesis of urethane acrylate (UA-2) Into a four-neck flask equipped with a stirrer, an air inlet tube, and a thermometer, the above-mentioned component A (number of repeating units of oxypropylene group = 9, hydroxyl value = 120 mg KOH / g)425g of hexamethylene diisocyanate (Kanto Chemical Co., Ltd., NCO content: 50% by weight), 75g of dibutyltin dilaurate, and 0.05g of dibutyltin dilaurate were added. The molar ratio of hydroxyl group (OH) / isocyanate group (NCO) was 1.05. Next, while blowing in air, the temperature inside the four-neck flask was kept at 60°C and reacted for 4 hours. After that, it was confirmed by the method of JIS K1603-1 that the isocyanate group content was 0.05% by weight or less and that almost all of the isocyanate groups had reacted with the hydroxyl groups to form urethane bonds, and 500g of urethane acrylate (UA-2) was obtained.

[0051] Comparative Example 2 Synthesis of urethane acrylate (UA-2') Instead of component A, component A' (number of repeating units of oxypropylene group = 9, hydroxyl value = 120 mg KOH / g) A urethane acrylate (UA-2') was synthesized in the same manner as in Example 2, except that the above was used.

[0052] Evaluation of urethane acrylate The low-temperature curing properties of the urethane acrylate obtained in Example 2 and Comparative Example 2 were evaluated using a viscoelasticity measuring device MCR302 (manufactured by Anton Paar). Specifically, 10 g of the urethane acrylate and 0.02 g of a thermal polymerization initiator ("V-65", 2,2'-azobis(2,4-dimethylvaleronitrile) manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were charged into a screw tube to prepare a reaction mixture. Then, the reaction mixture was heated, and the time from the time when the temperature reached 55°C to the time when the reaction mixture started to cure (i.e., the time when the storage modulus rose sharply) (referred to as "curing start time" in Table 2 below) was measured. After that, heating was continued at 55°C, and the time from the time when the curing started to the time when the storage modulus reached 1000 Pa (referred to as "curing time" in Table 2 below) was measured. The results are shown in Table 2.

[0053] [Table 2]

[0054] As shown in Table 2 ,Nari The curing initiation time and curing time of the urethane acrylate (UA-2) of Example 2 obtained using Part A were ,Nari It was shorter than that of the urethane acrylate (UA-2') of Comparative Example 2 obtained using the part A'.

[0055] As mentioned above, w b / w f The urethane (meth)acrylate of the present invention, which is a reaction product of a polyalkylene glycol mono(meth)acrylate that satisfies the relationship of formula (2) above and a polyisocyanate, has excellent thermosetting properties at low temperatures and can quickly reach a desired hardness from the start of curing. [Industrial Applicability]

[0056] The urethane (meth)acrylate of the present invention has good thermosetting properties at low temperatures and can quickly reach a desired hardness from the start of curing, making it useful for producing products including liquid crystal parts.

Claims

[Claim 1] A urethane (meth)acrylate which is a reaction product of component A and component B shown below: (Component A) Formula (1): CH 2 =CR-COO-(AO) n -H (1) In formula (1), R represents a hydrogen atom or a methyl group, AO represents at least one oxyalkylene group having 2 to 4 carbon atoms, and when two or more types of AO are present, (AO) n The addition form of may be either block or random, and n represents the average number of moles of oxyalkylene groups added and is a number from 5 to 100. is expressed by, and is calculated from a chromatogram obtained by gel permeation chromatography measurement. b And w f The ratio of b / w f But, formula (2): 0.25≦w b / w f ≦0.90 (2) (In formula (2), the retention time at the maximum peak height (h) in the peak of the chromatogram is t h The height of the maximum peak is 1 / 10 of the maximum peak height (h 1/10 ) two retention times at t f and t b (However, t f <t b ), then w f is h and f The difference between (t h -t f ), and w b is b and h The difference between (t b -t h ) is shown. A polyalkylene glycol mono(meth)acrylate satisfying the relationship: (Component B) Polyisocyanates.

Citation Information

Patent Citations

  • Improved polyether-containing double metal cyanide catalyst

    JP1997059373A

  • Production of functionalized polyethers

    JP2001514280A

  • Method for producing dmc catalyst

    JP2003531251A

  • Hydroxy-functional, copolymerizable polyalkylene glycol macromonomer, method for manufacturing it and use thereof

    JP2008106272A

  • Urethane (METH)acrylate and photocurable resin composition containing the same

    JP2014189735A